2009
DOI: 10.4070/kcj.2009.39.6.251
|View full text |Cite
|
Sign up to set email alerts
|

Complete Fracture of Sirolimus-Eluting Stent in a Saphenous Vein Graft to Left Anterior Descending Artery

Abstract: Coronary stent fractures have been suggested as a potential new mechanism of restenosis. The mechanical properties of stents were designed not only to prevent vessel recoil, but also to resist the mechanical stress of vessel movement over millions of cardiac cycles. We present a case in which mechanical stress may have contributed to the fracture of a stent implanted in a saphenous vein graft (SVG) to the left coronary artery. The patient was admitted due to chest pain 2 years after receiving a coronary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…However, SVG intervention is challenging because of the high rate of periprocedural myocardial infarction and restenosis 9). In addition, a stent in the SVG can fracture due to movement of the SVG 10). Recent reports have demonstrated that drug-eluting stents and embolic protection devices lead to good results in the management of SVG disease 11)12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SVG intervention is challenging because of the high rate of periprocedural myocardial infarction and restenosis 9). In addition, a stent in the SVG can fracture due to movement of the SVG 10). Recent reports have demonstrated that drug-eluting stents and embolic protection devices lead to good results in the management of SVG disease 11)12).…”
Section: Discussionmentioning
confidence: 99%
“… 9) In addition, a stent in the SVG can fracture due to movement of the SVG. 10) Recent reports have demonstrated that drug-eluting stents and embolic protection devices lead to good results in the management of SVG disease. 11) 12) Because a LIMA graft has high patency rate, LIMA intervention is not performed frequently.…”
Section: Discussionmentioning
confidence: 99%